Prostitution as Social Pathology: A Legal and Criminological Perspective - Sagala, Ermiyani; Sihotang, Natalia; Efendi, Zulmi; Febriyana, Arif (Law Research Review Quarterly, 2020)
These research aim to describe and analyze what are the factors behind a person's choosing to become Commercial Sex Workers (CSWs). In addition, this observation also aims to find out how people's perceptions or views about the existence of these CSWs around the community and their impact as well as what efforts have been made to eradicate this CSW in its shelter. This study used descriptive qualitative method. The object of research is the CSWs and the surrounding community. The sample used was purposive sampling, which is sampling based on specific objectives and considerations. Data collection techniques using interview techniques to informants conducted by non-participant observation which only observes and makes observations and documentation. Whereas to analyze the data used an interactive analysis model from Miles and Huberman namely data collection, data reduction, data presentation and conclusion drawing. The results of the study that the authors found in the field that the dominant factor that causes a person to work as a prostitute are economic factors. Economic factors in this case are difficult to meet their daily needs because there are no jobs that generate enough money to meet their daily needs. In addition to economic factors, there are also other factors such as the difficulty of finding work, low levels of education, income factors become more adequate sex workers to meet the needs and family factors.